2012
DOI: 10.1097/mpg.0b013e318261879d
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Real‐time Viewer for Endoscopic Deployment of Capsule Endoscope in the Pediatric Population

Abstract: The use of the RT viewer for endoscopic deployment of WCE is an effective technique to improve visualization of capsule placement in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Challenges include endoscopic placement in a patient with unusual anatomy as well as risk of retention in a patient with previous abdominal surgery . We have shown that use of the AdvanCE CE delivery device and a RT viewer during endoscopic placement of the capsule endoscope as was performed in all of these patients is useful for negotiating unusual anatomy such as seen after extensive abdominal surgery as in these patients . At our institution, the decision to perform CE is made in conjunction with medical and surgical teams so that, while every effort is made to avoid a situation which may result in a retained capsule, both the parents and the care teams are prepared to properly deal with capsule retention if it occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges include endoscopic placement in a patient with unusual anatomy as well as risk of retention in a patient with previous abdominal surgery . We have shown that use of the AdvanCE CE delivery device and a RT viewer during endoscopic placement of the capsule endoscope as was performed in all of these patients is useful for negotiating unusual anatomy such as seen after extensive abdominal surgery as in these patients . At our institution, the decision to perform CE is made in conjunction with medical and surgical teams so that, while every effort is made to avoid a situation which may result in a retained capsule, both the parents and the care teams are prepared to properly deal with capsule retention if it occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The given wireless video CE system with SB2 capsules and the given RT imager (Covidien Ltd., Yokneam, Israel) were used to perform the CE in all patients. Endoscopic placement with the assistance of the RT viewer was performed as described . All procedures were performed under general endotracheal anesthesia with the patient in the left lateral decubitus position.…”
Section: Methodsmentioning
confidence: 99%
“…Bass and Misiewicz1 used a real-time viewer to determine the delay in capsule transit, and used an endoscope to pass the capsule endoscope into the duodenum. However, in our case, the patient had significant food retention in the stomach, and thus this method would not be useful.…”
Section: Discussionmentioning
confidence: 99%
“…It causes minimal harm and is easily accepted by patients 1,2. However, bowel preparation can be limited and dangerous if the patients have active upper GI bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the routine use of real-time viewing is recommended post-ingestion to confirm that the capsule is within the gastrointestinal tract [435,436]. Every study should include real-time viewing 30-45 min after ingestion to confirm that the capsule has reached the duodenum; however, for those patients deemed to be at risk of aspiration or who develop symptoms, real-time viewing should be done immediately after the capsule has been swallowed to confirm gastric entry.…”
Section: Dysphagia and Diverticulamentioning
confidence: 99%